2008
DOI: 10.1007/s10162-008-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Responses of Vestibular–Nerve Afferents Innervating the Semicircular Canals in the C57BL/6 Mouse

Abstract: Extracellular recordings were made from vestibularnerve afferents innervating the semicircular canals in anesthetized C57BL/6 mice ranging in age from 4-24 weeks. A normalized coefficient of variation was used to divide afferents into regular (CV*G0.1) and irregular (CV*90.1) groups. There were three overall conclusions from this study. First, mouse afferents resemble those of other mammals in properties such as resting discharge rate and dependence of response dynamics on discharge regularity. Second, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 56 publications
(89 reference statements)
10
85
1
Order By: Relevance
“…The range of normalized CV* values obtained from mice of the present study is comparable to that reported for mouse canal afferents (Lasker et al 2008;Yang and Hullar 2007). The range of CVs as well as the mean CV for the OTO+ data closely approximate those reported in Figure 1 of Yang and Hullar (2007) for "wild-type" C57 mice (no significant difference, p90.2).…”
Section: Resting Discharge Regularity and Rates In Micesupporting
confidence: 89%
See 1 more Smart Citation
“…The range of normalized CV* values obtained from mice of the present study is comparable to that reported for mouse canal afferents (Lasker et al 2008;Yang and Hullar 2007). The range of CVs as well as the mean CV for the OTO+ data closely approximate those reported in Figure 1 of Yang and Hullar (2007) for "wild-type" C57 mice (no significant difference, p90.2).…”
Section: Resting Discharge Regularity and Rates In Micesupporting
confidence: 89%
“…These authors have argued that because CV for a given neuron can take on wide ranging values and because the curves of individual neurons tend not to intersect those of other neurons, cells may be uniquely ranked based on CV provided the comparison across neurons is made at the same discharge rate. For these reasons, procedures for normalizing CV for particular rates (generally designated CV*) have been developed and widely used e.g., Baird and Lewis 1986;Goldberg et al 1982Goldberg et al , 1990bLasker et al 2008;Yang and Hullar 2007). Here, we normalized CV to a 15-ms interval based on the coefficients of Baird et al (1988) for the chinchilla and on those of Lasker et al (2008)for the mouse.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…In addition, the arguments outlined above assume that either of the response dynamics of vestibular neurons or the statistics of natural vestibular stimuli are similar between humans and monkeys. Although comparison of vestibular neuron response properties across amniotes has revealed striking similarities (Fernández and Goldberg, 1971;Hullar et al, 2005;Sadeghi et al, 2007;Yang and Hullar, 2007;Lasker et al, 2008), further studies conducted in monkeys will be needed to test whether the statistics of natural vestibular stimuli are similar to those reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this early maturation depends on the initial growth of the animal. Hence the size of the vestibular organs, in particular of the semicircular canals, is a biomechanical constraint for the detection of the head movements (Muller, 1999;Yang and Hullar, 2007;Lambert et al, 2008;Lasker et al, 2008). In rats, the semicircular canals have reached ∼75% of their size at birth (Curthoys, 1979b).…”
Section: Acquisition Of the Vestibulo-ocular Reflex And Other Gaze Stmentioning
confidence: 99%